Conceptual and Juridical Review of the Destruction of Cultural Property in the Ukraine - Russia War - Putri, Maria Kunti Atika; Wattimena, Keanu Abinuno (Universitas Negeri Surabaya, 2024)
The ongoing conflict between Ukraine and Russia has witnessed numerous war crimes, notably the destruction of cultural property belonging to Ukraine, despite international protections afforded to such sites. This paper undertakes a conceptual and juridical review of the protection of cultural property during armed conflict, specifically examining its application in the context of the Ukraine-Russia war. Employing a doctrinal research method, the study elucidates the significance of safeguarding cultural heritage, which is deemed a global inheritance. The analysis emphasizes the provisions outlined in the 1954 Hague Convention, which governs the protection of cultural property, and explores the respective responsibilities of Ukraine and Russia in addressing instances of cultural destruction. By evaluating these legal frameworks and their application, this research contributes to understanding the obligations and challenges related to preserving cultural heritage amidst contemporary armed conflicts, advocating for adherence to international norms and facilitating mechanisms for resolution and accountability.